Pengaruh Content Marketing dan Brand Awareness terhadap Keputusan Pembelian Produk Parfum Freshchubs di Kota Surabaya - Gracia Aprina Chita Rahayu; Siti Aminah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Currently, technology & information is experiencing rapid development due to the technology-aware behavior of society. With the development of technology today, all aspects of life require assistance from technology. This includes businesses in Indonesia. The purpose of this research is to determine whether content marketing and brand awareness in the city of Surabaya influence the purchase decision of Freshchubs perfume products. The sample in this study consisted of people in the city of Surabaya aged 17 years and above who have purchased Freshchubs products, totaling 78 respondents, using the purposive sampling method. The questionnaire method was used as the data collection method in this study. From the 78 respondents, it is shown that content marketing and brand awareness have a positive influence and significant on purchasing decisions.